2003
DOI: 10.1111/j.1750-3639.2003.tb00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Phosphorylated ERK/MAP Kinases to Mitochondria and Autophagosomes in Lewy Body Diseases

Abstract: We previously found that sustained ERK activation contributes to toxicity elicited by the parkinsonian neurotoxin 6-hydroxydopamine. In addition, substantia nigra neurons from patients with incidental Lewy body disease, Parkinson's disease (PD), and diffuse Lewy body dementia (DLB) display abnormal phospho-ERK accumulations in the form of discrete cytoplasmic granules. In this study, we investigated the subcellular localization of phospho-ERK immunoreactive granules using double label confocal microscopy and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
177
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 239 publications
(191 citation statements)
references
References 54 publications
10
177
0
4
Order By: Relevance
“…A previous study showed that persistent glutamate-induced ERK1/2 activation promotes cell death in a hippocampal cell line and primary neurons [39] . Abnormal activation of ERK1/2, along with interactions with abnormal mitochondria, is present in the substantia nigra in the brains of PD patients [40] . Moreover, the inhibition of ERK1/2 activation could reduce 6-OHDAinduced cell death [37] .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that persistent glutamate-induced ERK1/2 activation promotes cell death in a hippocampal cell line and primary neurons [39] . Abnormal activation of ERK1/2, along with interactions with abnormal mitochondria, is present in the substantia nigra in the brains of PD patients [40] . Moreover, the inhibition of ERK1/2 activation could reduce 6-OHDAinduced cell death [37] .…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of autophagosomes has been observed during the early stages of many neurodegenerative disease, such as Alzheimer's disease (Yu et al, 2005), prion disease (Sikorska et al, 2004), Parkinson's disease (Zhu et al, 2003), and Huntington's disease (Li et al, 2001). In addition, autophagosomes are reportedly accumulated in neurons after hypoxia-ischemia (Koike et al, 2008), brain injury (Diskin et al, 2005), and glutamate application (Borsello et al, 2003;Sadasivan et al, 2006).…”
Section: Conversely Glud2mentioning
confidence: 99%
“…17,18,20 Recent studies have reported that deregulation of autophagy was implicated in PD. 21,22 Autophagosome accumulation is evident in the brain tissues of PD patients 23,24 and in MPTP-induced PD animal models. 25 Moreover, PINK1 (PTEN induced putative kinase 1)-and PARK2/parkin (parkin RBR E3 ubiquitin protein ligase)-mediated autophagy is actively involved in selective clearance of damaged mitochondria and protection of the neurons from death.…”
Section: Introductionmentioning
confidence: 99%